Soil macrofauna abundance and soil characteristics of limestone post-mining land in Bogor, West Java, Indonesia - BASUKI WASIS; FERNANDA REZA PUTRA; BAYU WINATA; ERIANTO INDRA PUTRA; GRAHAME APPLEGATE (Society for Indonesian Biodiversity, 2025)
Abstract. Wasis B, Putra FR, Winata B, Putra EI, Applegate G. 2025. Soil macrofauna abundance and soil characteristics of limestone post-mining land in Bogor, West Java, Indonesia. Biodiversitas 26: 314-5323. Limestone mining can lead to the loss of soil fauna and a decline in soil quality on post-mining land. Soil, as a key component of forest ecosystems, exhibits distinct characteristics across site types. Revegetation is an important strategy to restore ecosystems and biodiversity through tree planting. This study, which aimed to assess the abundance of soil macrofauna, characterize site conditions, and evaluate the influence of soil properties on macrofauna abundance in the limestone post-mining area of PT Solusi Bangun Indonesia, Narogong, Bogor District, West Java, Indonesia, has yielded significant findings. Soil macrofauna were collected using hand sorting and hand capture methods, while biodiversity indices were calculated. Undisturbed soil samples (ring samples) were used for physical property analysis, and disturbed samples (0-20 cm depth) were used for chemical and biological analyses. Data were analyzed using Least Significant Difference (LSD) and negative binomial regression analysis. Macrofauna abundance in Old Revegetation 2010 (OR) sites (54±18.4 individuals) was significantly higher than in Open post-mining land (O) (0.5±0.7) and Young Revegetation 2018 (YR) sites (3.5±2.1) researched in 2023. Porosity, organic carbon, soil pH, soil respiration, and dry litter weight showed significant positive correlations with macrofauna abundance, while soil temperature had a significant negative correlation. These findings, which underscore the importance of revegetation and the role of soil macrofauna as an indicator of post-mining soil quality recovery, are of significant interest to the scientific community and conservation practitioners.